Case Report of Esophageal Rupture, Empyema, and Aortic Dissection Potentially Caused by Severe Vomiting - Jiawen Huang; Chengfeng Huang; Zhaoming Lin; Huanan Liu; Xiaoshen Zhang; Tianyu Xu; Xiaoxia Fu (Cardiology Discovery)
Abstract. Both empyema and type A aortic dissection are life-threatening conditions. The combination, though rare, can cause serious complications and death. There have been rare cases of empyema caused by a co-infection with a Gram-positive bacterium, Granulicatella adiacens, which is difficult to identify, and a Gram-negative bacterium, Escherichia coli. In this case, a 50-year-old man was referred to the emergency department due to sudden chest pain and a suspected diagnosis of type A aortic dissection. The patient was subsequently found to have co-morbid empyema and a fissure in the esophagus when the cause of the disease was investigated. Considering the possibility that the patient's infection was of digestive origin, a combination of Gram-positive and Gram-negative antibiotics was given immediately. Etiological examination later confirmed the presence of Granulicatella adiacens and Escherichia coli in chest drainage fluid, and the patient was successfully treated with antimicrobial therapy and conservative treatment.